Alcohol‐free and low‐alcohol beers: Aroma chemistry and sensory characteristics. Issue 1 (18th November 2022) - Piornos, José A.; Koussissi, Elisabeth; Balagiannis, Dimitrios P.; Brouwer, Eric; Parker, Jane K.
Abstract: Alcohol‐free beers have gained popularity in the last few decades because they provide a healthier alternative to alcoholic beers and can be more widely consumed. Consumers are becoming more aware of the benefits of reducing their alcohol consumption, and this has increased the sales of nonalcoholic alternatives. However, there are still many challenges for the brewing industry to produce an alcohol‐free beer that resembles the pleasant fruity flavor and overall sensory experience of regular beers. The aim of this review is to give a comprehensive overview of alcohol‐free beer focusing on aroma chemistry. The formation of the most important aroma compounds, such as Strecker aldehydes, higher alcohols, and esters, is reviewed, aiming to outline the gaps in current knowledge. The role of ethanol as a direct and indirect flavor‐active compound is examined separately. In parallel, the influence of the most common methods to reduce alcohol content, such as physical (dealcoholization) or biological, on the organoleptic characteristics and consumer perception of the final product, is discussed.